An investigation into the sub-categories of “attitude” in the book the world is flat by thomas l. Friedman from the perspective of appraisal theory (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The present study explores sub-categories of Attitude -Affect, Judgement and Appreciation- in the book “The World is Flat” by Thomas L. Friedman in the light of Appraisal Theory. The study aims to investigate the syntactic and semantic realizations of Attitude sub-categories from 358 samples collected from the book. The thesis employed the descriptive method to fully describe the realizations of Attitude sub-categories in terms of syntax and semantics to obtain the setting goals. The finding of the research demonstrate that Attitude sub-categories can be recognized in various group and phrase structures in which nominal groups and adjective groups are more favourable. The study also works out typical functions of Attitude sub-categories as components in transitivity processes. Semantically, the findings show that all Appraisal evaluating criteria were reflected in the book and significantly the positive values are dominant. This is the interpersonal meaning which the book contributes to nurture its readers’ insights to the reality of the world in the era of digital technology. The study makes a significant contribution to our understanding of the sub-categories of Attitude in the book and provides the teachers and university students majoring in English with practical implication to evaluate a discourse fragment and interpret a discourse fragment in the light of Appraisal Theory and in line with Systemic Functional Linguistics.